Advances and gaps in studies on healthy meat products and their relationship with regulations: The Brazilian scenario - Rios-Mera, Juan D.; Saldaña, Erick; Patinho, Iliani; Selani, Miriam M.; Contreras-Castillo, Carmen J. (Trends in food science & technology, 2021)
Strategies for the reformulation of meat products respond to consumers’ demand for healthier food alternatives. The reduction of salt or sodium and animal fat, and the substitution of synthetic antioxidants by natural ones have been a subject of study for Brazilian researchers for many years, but the industrial application of new technological alternatives presents the challenge of adapting to regulations related to the processing of meat products. Reports by Brazilian researchers from 2011 to 2019 were collected from the Scopus database and their abstracts were submitted to a textual analysis to visualize the trend of studies over these years. The relationship between the approaches/ingredients proposed in the studies and the Brazilian regulation was discussed. Numerous alternatives for natural antioxidants and salt and animal fat substitutes have been proposed, but Brazilian regulation is restrictive with respect to the use of natural antioxidants and the most studied salt substitute in meat products. However, studies using alternatives more compatible with Brazilian regulations have been proposed. For industrial application purposes, some flavorings and spices may have antioxidant activity and act as natural antioxidants, delaying the lipid oxidation of meat products; the sodium content can be reduced using several morphologies or sizes of salt particles; and the incorporation of oils rich in polyunsaturated fatty acids, embedded in oleogels and microparticles using encapsulating proteins, seem to be a viable alternative for reducing animal fat in meat products. •Brazilian research on healthy meat products was analyzed by textual analysis.•Natural antioxidants, salt and animal fat reduction were addressed.•The new ingredients proposed were discussed in relation to Brazilian regulation.•Brazilian regulation is restrictive for natural antioxidants and salt substitutes.•New studies compatible to Brazilian regulation are proposed.